THE EFFECT OF SHOWING SHORT VIDEOS ON CHILDREN'S LISTENING SKILLS - Mufida Illah Ilmiah, Yahmun Yahya (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This study investigates the impact of short video presentations on children's listening skills. Early childhood is a critical period for brain and language development. With the rise of digital technology, short videos from platforms like YouTube and TikTok have become prominent in children's lives. This research aimed to determine the effect of watching short videos on listening skills among students at UPT Satuan Pendidikan SDN Pusungmalang I in Pasuruan Regency. A quantitative approach was used, involving 28 students selected through simple random sampling. Data were collected via observations, questionnaires, literature study, and internet research, and analyzed using normality, linearity, heteroscedasticity tests, and simple linear regression analysis. Results indicated that short videos significantly enhance children's listening abilities, including pronunciation, comprehension, and accuracy. However, challenges such as limited internet access and technical issues were noted. The study concludes that short videos positively influence listening skills and recommends integrating them into educational programs to optimize learning outcomes.